Um estudo intergeracional sobre autonomia e iniciação sexual de universitárias e suas mães - Donati, Fabiana Augusta [UNESP] (2015)
The autonomy over their own decisions and especially in relation to sexuality and sexual initiation are issues of concern to educators, families and society in general, specifically when dealing with young women. Trying to understand the intergenerational dynamics, that exist between mothers and daughters, in this context, this study was part of a larger study that investigated the intergenerational education on autonomy and sexual initiation among university students from a private institution in the interior of São Paulo. We conducted a baseline survey in order to identify the behavioral patterns of students and the instrument used was a quantitative closed questionnaire that surveyed the sexual behavior, socioeconomic status, marital status, religion and condom use. The questionnaire was applied to 218 students from six courses in the humanities and health. Regarding the affective situation of the students, 43.5% were in stable relationships - dating, 29.9% were single or with someone and 26.6% were married students. Most students were classified as young according to the categorization of Statute of Youth (aged 15 to 29 years), comprised 75.0% of the research participants. Of the students who reported sexual life, 187 participants, the average age of sexual initiation of these university students was 17, and in relation to condom use at first sexual intercourse, 66.7% of young women reported using and about last relationship this percentage dropped to 35.3%. With regard to religion 47.2% declared themselves catholic, 13.7% spiritualists and 33.5% evangelical. The results showed a large number of students with active sexual life, regardless of socioeconomic level and area of expertise. A greater mother-daughter interaction was observed in the intergenerational dynamics in more autonomous participants, but this data was not considered unique for autonomy. The assumption that sexual initiation occurred in an autonomous way is...